2019
DOI: 10.1002/mrm.28101
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative comparison between a navigated Cartesian and a self‐navigated radial protocol from clinical studies for free‐breathing 3D whole‐heart bSSFP coronary MRA

Abstract: Purpose Navigator‐gated 3D bSSFP whole‐heart coronary MRA has been evaluated in several large studies including a multi‐center trial. Patient studies have also been performed with more recent self‐navigated techniques. In this study, these two approaches are compared side‐by‐side using a Cartesian navigator‐gated and corrected (CNG) and a 3D radial self‐navigated (RSN) protocol from published patient studies. Methods Sixteen healthy subjects were examined with both sequences on a 1.5T scanner. Assessment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
9
1
Order By: Relevance
“…Moreover, we did not compare the proposed CMRA technique to the widely available Cartesian respiratory navigator gated CMRA method as CTA, an independent reference standard, was available in our patients. A previous study in healthy subjects investigating coronary arteries demonstrated signal homogeneity and time efficiency with the self-navigated technique, but inferior vessel sharpness [44]. Although, no vessel sharpness quantification was performed in the current study, we also did not visually observe limited sharpness when evaluating the aorta.…”
Section: Discussioncontrasting
confidence: 61%
“…Moreover, we did not compare the proposed CMRA technique to the widely available Cartesian respiratory navigator gated CMRA method as CTA, an independent reference standard, was available in our patients. A previous study in healthy subjects investigating coronary arteries demonstrated signal homogeneity and time efficiency with the self-navigated technique, but inferior vessel sharpness [44]. Although, no vessel sharpness quantification was performed in the current study, we also did not visually observe limited sharpness when evaluating the aorta.…”
Section: Discussioncontrasting
confidence: 61%
“…These sequences offer inherent high contrast between blood and background tissues, thereby allowing for optimal delineation of the aortic lumen [ 8 , 19 ] and accurate, reproducible pre-operative monitoring of aortic root diameters [ 1 , 15 , 20 , 21 ]. However, several limitations are intrinsic to this approach [ 22 , 23 ]. Conventional 3D bSSFP CMRA techniques use diaphragmatic respiratory gating (dNAV) to minimize the effects of respiratory motion in the images, which results in unpredictable and excessively long acquisition times [ 22 ] and the risk of incomplete or aborted scans because of respiratory drift [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a reference for comparison, the average (N = 10) specific absorption rate for a triggered 3D Cartesian single‐phase coronary MRI scan at 1.5T using the protocol in ref. was 1.0 ± 0.1 W/kg. In general, a large difference in image quality was observed when comparing FISS to bSSFP (Figures ), with the former demonstrating markedly reduced streak artifact.…”
Section: Resultsmentioning
confidence: 97%